Developing pre-service teachers intercultural communication competence: Learning through extracurricular informal digital learning of English - Nur Arifah Drajati; Lynde Tan; Surya Agung Wijaya; Agustina Tyarakanita (Studies in English Language and Education, 2024)
Intercultural communication and language proficiency have become increasingly essential in preparing Indonesian EFL pre-service teachers (PSTs) for cultural diversity. Indonesian EFL PSTs only communicated English to people with the same majors or educational background. This study explores the implication of developing PSTs intercultural communication competence (ICC) at one of the universities in Indonesia that designed and implemented informal digital learning of English (IDLE) as an extracurricular program. Thirty-seven university PSTs from various multicultural backgrounds with insufficient overseas experiences (such as exchange programs or internship programs) participated in this study. We conducted the study for one semester during the pandemic, where the PSTs mainly communicated in online environments. Combining the analysis from observations, artifacts, diaries, and interviews, this study reports that engaging in extracurricular IDLE potentially unlocked PSTs to 1) become aware of the value of their own cultural background and biases in developing their perception of other cultures and 2) evaluate their English language choices that potentially affected on how they addressed some topics and interpretation with overseas friends (OFs). Furthermore, this study provides insight into the benefits of implementing ICC for PSTs, especially in language development, and how they perceived this as a motivation for designing their future classroom practices.